Arsenomics of exiguobacterium sp PS (NCIM 5463) - Sacheti, Poonam; Bhonsle, Hemangi S.; Patil, Rajendra; Kulkarni, Mahesh J.; Srikanth, Rapole; Gade, Wasudeo N. (RSC Advances, 2013)
In the present study, arsenate [As(V)] tolerant organisms were isolated from a metal contaminated site, and identified by 16S rDNA sequencing as Exiguobacterium sp. Arsenomics (omics of arsenic response) in Exiguobacterium sp. PS via two-dimensional gel electrophoresis (2-DGE) coupled with identification of proteins using MALDI-TOF MS, MALDI-TOF MS/MS and LC/MSE are studied vide this paper. Out of 2460 Coomassie stained proteins, 270 were differentially expressed (p < 0.05). Considering the resolution and abundance level, 45 spots (proteins) were subjected to MALDI-TOF MS/MS, MALDI-TOF/TOF and LC/MSE. Out of these, 33 were identified and categorized into several functional categories (including both known and novel/putative stress responsive proteins) viz., carbohydrate and energy metabolism, stress response, motility, amino acid, and purine and protein synthesis. The identifications of unique proteins, phosphate ABC transporter ATPase subunit and pyridine nucleotide disulfide oxidoreductase, are the significant findings of the present study which may be used as markers of As(V) stress in Exiguobacterium sp. PS. The absence of As(V) reductase activity and non-amplification of the arsC gene of the ars operon suggests that the classical mechanism of As(V) resistance may not be operating in Exiguobacterium sp. PS. Lastly, considering the fact that proteomic studies under As(V) stress were performed only in Gram negative organisms, this study is the first comprehensive endeavour to explore the mechanism of As(V) response in Gram positive organisms, Exiguobacterium sp. PS at the proteomic level.